Genetic screens identify a context-specific PI3K/p27Kip1 node driving extrahepatic biliary cancer - Falcomatà, Chiara; Bärthel, Stefanie; Ulrich, Angelika; Diersch, Sandra; Veltkamp, Christian; Rad, Lena; Boniolo, Fabio; Solar, Myriam; Steiger, Katja; Seidler, Barbara; Zukowska, Magdalena; Madej, Joanna; et al. (Cancer discovery, 2021)
Biliary tract cancer ranks among the most lethal human malignancies, representing an unmet clinical need. Its abysmal prognosis is tied to an increasing incidence and a fundamental lack of mechanistic knowledge regarding the molecular basis of the disease. Here, we show that the Pdx1-positive extrahepatic biliary epithelium is highly susceptible toward transformation by activated PIK3CAH1047R but refractory to oncogenic KrasG12D. Using genome-wide transposon screens and genetic loss-of-function experiments, we discover context-dependent genetic interactions that drive extrahepatic cholangiocarcinoma (ECC) and show that PI3K signaling output strength and repression of the tumor suppressor p27Kip1 are critical context-specific determinants of tumor formation. This contrasts with the pancreas, where oncogenic Kras in concert with p53 loss is a key cancer driver. Notably, inactivation of p27Kip1 permits KrasG12D-driven ECC development. These studies provide a mechanistic link between PI3K signaling, tissue-specific tumor suppressor barriers, and ECC pathogenesis, and present a novel genetic model of autochthonous ECC and genes driving this highly lethal tumor subtype. - Significance: We used the first genetically engineered mouse model for extrahepatic bile duct carcinoma to identify cancer genes by genome-wide transposon-based mutagenesis screening. Thereby, we show that PI3K signaling output strength and p27Kip1 function are critical determinants for context-specific ECC formation.
Gesehen am 19.01.2022
Im Titel ist der Ausdruck "Kip1" hochgestellt